Executive skills - Minkoff, Philip (English language teaching (Englewood Cliffs, N.J.), 1994)
This text is aimed at people who already have, or will one day have, managerial responsibilities and who wish to develop their business skills within the English language context. As well as improving their interactive language, students develop communications skills through case studies, role playing, problem solving and working with statistics. Many activities are designed to incorporate the students' own professional experience and theoretical knowledge.